Susceptibilidad a deslizamientos en las áreas mineras Bella Rica código 15 y Guanache-Tres de mayo código 170, cantón Camilo Ponce Enríquez, provincia del Azuay. - Ruilova Prado, Julio Patricio (2015)
This thesis raises the identification of areas of landslide susceptibility in the mining areas BELLA RICA Cod. 15 and GUANCHE - TRES DE MAYO, Cod.170, located in Canton Camilo Ponce Enriquez, Azuay Province, to the southwest of Ecuador.Has conducted the analysis following the heuristic method, corroborating research with Deterministic method of geotechnical variables of the study sector. For the preparation of this work, a set of technical parameters both data collection field and office, among which we can mention the topographic, geological, geomorphological survey was conducted. They were taken into account variables such as geomorphology, geology, vegetation and slope coverage, thematic maps of each of the aforementioned variables were developed and thus assess the intervention in the processes of landslides. With the help of GIS (ArcGIS 10.1) are processed each variables in digital form for overlaying thematic maps and get the landslide susceptibility map, which includes five categories: very low, low, medium, high and very high susceptibility; accounting for 68.56%, 23.61%, 6.72%, 1.02% and 0.09% respectively of the study area. The results of this research will be useful for Gold Mining Cooperative Production "Bella Rica", owner of the Bella Rica and Guanache areas - Tres de Mayo, to the work location and postage future mining operations, with projection technical parameters, which ensure profitability and security of staff working in these areas, and minimizing environmental damage.